2013
DOI: 10.2139/ssrn.2271349
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Choices for Redistribution and the Veil of Ignorance: Theory and Experimental Evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…3 Importantly, this third-party impartiality procedure is not equivalent to the Rawlsian "veil of ignorance" (Rawls 1971), because spectators' earnings in the experiment are completely unrelated to their allocation decisions. We deliberately did not choose a "behind the veil of ignorance" approach because it has been shown that the type of uncertainty entailed by the veil of ignorance influences individuals' allocation behavior by introducing insurance purposes (Aguiar et al 2010, Schildberg-Hörisch 2010 and strategic considerations (Gerber et al 2014). there is no uncertainty for both recipients, we expect all spectators to choose the equal split. However, will this also be the case when a recipient is exposed to uncertainty?…”
Section: Introductionmentioning
confidence: 99%
“…3 Importantly, this third-party impartiality procedure is not equivalent to the Rawlsian "veil of ignorance" (Rawls 1971), because spectators' earnings in the experiment are completely unrelated to their allocation decisions. We deliberately did not choose a "behind the veil of ignorance" approach because it has been shown that the type of uncertainty entailed by the veil of ignorance influences individuals' allocation behavior by introducing insurance purposes (Aguiar et al 2010, Schildberg-Hörisch 2010 and strategic considerations (Gerber et al 2014). there is no uncertainty for both recipients, we expect all spectators to choose the equal split. However, will this also be the case when a recipient is exposed to uncertainty?…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with dictator and ultimatum games, there is no obvious "fair" ex-post allocation of payoffs in our model, 8 pro-social behavior at the constitutional stage cannot be exclusively attributed to concerns about the fairness. 9 Indeed, our results 8 For recent experiments on fairness concerns and voting, see, e.g., Gerber et al (2013) and Hoechtl et al (2012). 9 Implementing the simple majority rule maximizes the aggregate payoffs in a given round and might hence be preferred by players with efficiency preferences.…”
Section: Hypothesesmentioning
confidence: 76%
“… 8 For recent experiments on fairness concerns and voting, see, e.g., Gerber et al (2013) and Hoechtl et al (2012). …”
mentioning
confidence: 99%
“…We deliberately did not choose a 'behind the veil of ignorance' approach because it has been shown that the type of uncertainty entailed by the veil of ignorance influences individuals' allocation behavior by introducing insurance purposes (Aguiar et al 2010, Schildberg-Hörisch 2010 and strategic considerations (Gerber et al 2014). equal split. However, will this also be the case when a recipient is exposed to uncertainty?…”
Section: Introductionmentioning
confidence: 99%